Light Pipe Transporter for High-rise Office Building in Tropical Climate (International Journal of Built Environment and Sustainability, 2016)
Daylight has known to bring benefits for human, psychologically and physiologically. It also provides better indoor environment quality and thus increase the performance and productivity of office workers as stated by Paevere (2009). However, due to economic reasons, the current practice of using deep open plan building has cause a dent to having daylight in the interior spaces, which cause a dependency on artificial lighting. Hence, to provide daylight in deep interior, light distribution system is needed. Although so, according to Hansen (2003), most of the systems can only illuminate up to 8m-10m depth. Therefore, light pipe (LP) plays an essential role where it can illuminate up to 20m depth. LP’s efficiency depends on the 3 main components; collector, transporter and extractor. This research explores the effectiveness of horizontal LP through different type of transporter’s shapes which includes rectangular, triangular, square and semi-circle. Previous studies have shown differences of efficiency on the shaped while using vertical LP. This research’s analysis was done using a computer simulation, Integrated Environment Solution: Virtual Environment (IESVE), where DF of each shapes were compared to MS 1525:2007 benchmark. The viability of the software was also validated though an assessment with a physical scaled-model experiment that was conducted in an open car park in Universiti Teknologi Malaysia, Johor, Malaysia. The results from the simulation showed that semi-circle shaped transporter offered the same efficiency as rectangular shaped. These findings will promote the usage of LP in buildings as it decreases the costing for LP.